Quando la medicina uccide il pensiero: miseria dell’organicismo - Gigli, Beniamino; Montibeller, Marcello (Il sogno della farfalla, 2005)
This article discusses the epistemological problems stemming from the application of a reductionist vision of the body-mind relationship in psychiatry. The method followed involves applying logicalepistemological analytical models to data contained in recent medical literature and evidentiating their philosophical substratum. The article proposes essentially two theses: 1) the logical impossibility of an explanatory reduction of particular mental states to brain states in virtue of the principle of subdetermination; 2) the inapplicability of an information model to the mind, as a result of the non-seperability of the programme from the structure, as far as the brain is concerned. Making reference to Fagioli’s teory, insofar as it is able to give both a non-reductionistic explanation of the biological origin of the mind, the article concludes that it is necessary to redefine the theoretical approach to the mind-body problem and consequently the therapeutic approach to mental health.